2005
DOI: 10.1099/vir.0.81063-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable trimerization of recombinant rabies virus glycoprotein ectodomain is required for interaction with the p75NTR receptor

Abstract: Native rabies virus glycoprotein (RVGvir) is a trimeric, membrane-anchored protein that has been shown to interact with the p75 NTR neurotrophin receptor. In order to determine if the RVG trimeric oligomerization state is required for its binding with p75 NTR , different soluble recombinant molecules containing the entire RVG ectodomain (RVGect) were expressed alone or fused at its C terminus to the trimerization domain of the bacteriophage T4 fibritin, termed 'foldon'. The oligomerization status of recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 47 publications
1
35
2
1
Order By: Relevance
“…Consistent with this view, we have demonstrated that RVG trimerization is required for p75 NTR interaction (46) and that RVG interacts with the oligomeric but not with the monomeric form of p75 NTR (C. Tuffereau, unpublished results). These results suggest the need for a 3-to-3 complex for efficient binding.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with this view, we have demonstrated that RVG trimerization is required for p75 NTR interaction (46) and that RVG interacts with the oligomeric but not with the monomeric form of p75 NTR (C. Tuffereau, unpublished results). These results suggest the need for a 3-to-3 complex for efficient binding.…”
Section: Discussionsupporting
confidence: 63%
“…First, p75 NTR might require a cofactor that is not found in these neurons. This is unlikely, because we have shown that a soluble form of p75 NTR is able and sufficient to interact with RV and RVG on its own (31,46) and its affinity constant is 2 nM (46). Second, binding of RV is prevented, and there are several molecules which are tightly associated with p75 NTR and could modify its binding affinity (14).…”
Section: Discussionmentioning
confidence: 97%
“…Also, the G glycoprotein from rabies virus is a relatively complex trimeric, membrane-anchored protein (Sissoëff et al 2005), and the expression of membrane proteins is not a simple process (Grisshammer 2006). In the case of transmembrane proteins, folding occurs in three different environments: the endoplasmic reticulum (ER) lumen, the ER membrane and the cytosol.…”
mentioning
confidence: 99%
“…It has been shown that G can be found in three different states, a "native" state, an activated hydrophobic state and a fusion inactive conformation. Antigenic differences between these forms have been reported [10][11][12]. The immune protection mounted during rabies vaccination is considered to be very much dependent on the virus G, inducing virus neutralizing antibodies, production of T helper, cytotoxic T cells and protection against intracerebral challenge [13][14][15][16].…”
mentioning
confidence: 99%